SOCIOECONOMIC AND TECHNOLOGICAL CHARACTERIZATION OF MEAT SHEEP PRODUCTION SYSTEMS IN THE STATE OF PARANÁ, BRAZIL - Debortoli, Elisio de Camargo; Monteiro, Alda Lúcia Gomes; Gameiro, Augusto Hauber (Archives of Veterinary Science, 2022)
Sheep farming has shown organizational and development initiatives since the beginning of the 21st century in the State of Paraná. This study identified and characterized the meat sheep production system profile in five mesoregions of the State of Paraná. The study sample was defined and selected by using the rapid appraisal methodology, which was applied in five mesoregions of Paraná State. These mesoregions together account for 65.22% of the sheep population of the State. Data were collected by means of a semi-structured questionnaire applied during visits to these farms with the support of technicians from the Federation of Agriculture of the State of Paraná (FAEP) as well as local technical assistants, addressing the following aspects: (i) farm, farm owner and labor profile, (ii) flock characteristics, (iii) production and feeding systems, (iv) facilities, (v) reproductive and sanitary management, (vi) challenges and future prospects. The results obtained revealed the occurrence of a production system heterogeneity and difficulties in defining standards for the activity development. However, positive prospects were also identified, such as: the use of crop-livestock integrated systems, the farmers' intention to keep their businesses and the importance of cooperative organizations in the production process coordination.